2016
DOI: 10.1016/j.jneuroim.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen induces multiple regulatory B cell subtypes and promotes M2 microglia and neuroprotection during experimental autoimmune encephalomyelitis

Abstract: Sex hormones promote immunoregulatory effects on multiple sclerosis. The current study evaluated estrogen effects on regulatory B cells and resident CNS microglia during experimental autoimmune encephalomyelitis (EAE). Herein, we demonstrate an estrogen-dependent induction of multiple regulatory B cell markers indicative of IL-10 dependent as well as IFN-γ dependent pathways. Moreover, although estrogen pretreatment of EAE mice inhibited the infiltration of pro-inflammatory cells into the CNS, it enhanced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 50 publications
6
53
0
Order By: Relevance
“…In agreement with previous results in EAE model (Pifarre et al 2014), recent studies have shown that the increased expression of IL-10 and promotion of M2 microglia phenopype after estrogen treatment promotes neuroprotection preventing EAE progression (Benedek et al 2016). Moreover, it has been shown that IL-10 increase expression resulted in attenuated inflammatory response, decreased microglia activation and less neurodegeneration in EAE model (Mayo et al 2016).…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with previous results in EAE model (Pifarre et al 2014), recent studies have shown that the increased expression of IL-10 and promotion of M2 microglia phenopype after estrogen treatment promotes neuroprotection preventing EAE progression (Benedek et al 2016). Moreover, it has been shown that IL-10 increase expression resulted in attenuated inflammatory response, decreased microglia activation and less neurodegeneration in EAE model (Mayo et al 2016).…”
Section: Discussionsupporting
confidence: 90%
“…E2 pretreatment protected intact female C57B/6 mice, as previously reported (Benedek et al 2016). Male and OVX female C57B/6 mice were also significantly protected from EAE when E2 was administered 7 days prior to the induction of EAE compared to sham treated controls (Fig.…”
Section: Resultssupporting
confidence: 84%
“…The frequency of CD4 + T cells was unchanged in male mice treated with E2 compared to sham treated mice (Fig 2b). Unlike B cells and T cells, the frequency of CD11b + (monocytes/macrophages) was significantly decreased in E2 treated OVX females and males (Fig 2a, p<0.05 and Fig 2b, p<0.0001), respectively, whereas intact female mice showed no significant difference in the frequency of CD11b + cells between E2 and sham treated mice (Benedek et al 2016). …”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations